Marital Quality and Hardiness on Parenting Stress in Couples with Children on the Autistic Spectrum - Istikomah, Fatonah; Nurhayati, Siti Rohmah (Psychological Research and Intervention, 2021)
Literature  review  and  preliminary  research  show  that  there  is  a  tendency  for  parents  who  have children with the autistic spectrum to experience parenting stress. On the other hand, there is a tendency for married couples who are not united and have low marital quality, and parents are discouraged when caring for children with the autistic spectrum. Therefore, this study aims to examine the effect of marital quality  and  hardiness  on  parenting  stress  in  parents  who  have  children  on  the  autistic  spectrum. Quantitative research with a survey method, the research sample amounted to 31 respondents who were determined  by  the  saturated  sampling  method.  The  research  used  instruments,  namely,  the  parenting stress  index-short  form  (PSI-SF)  scale  by  Abidin,  the  Dispositional  Resilience  Scale  (DRS-15)  by Bartone,  and  the  marriage  quality  scale  by  Nurhayati.  The  data  analysis  technique  is  multiple  linear regression analysis. The results of the study, the quality of marriage has no effect on parenting stress with a value of t = 0.288; sig= 0.776.personality Hardiness has an effect on parenting stress with a value of t= -2.155;  sig=  0.040.  Marital  quality  and  hardiness  have  no  simultaneous  effect  on  parenting  stress  on parents with autistic spectrum children with a value of F= 2,632; sig= 0.090